Analisis Bakteri E. Coli dan Lingkungan Fisik Terhadap Kualitas Pengolahan Air Minum Isi Ulang - Asma, Asma; Ramlan, Ramlan; Majid, Abdul; Majid, Makhrajani; Usman, Usman (Media Literasi Indonesia, 2025)
The high demand for refill drinking water by many people has led to many sales activities for refill drinking water and it is easier to find. The purpose of this study was to determine the E.coli bacteria and the physical environment on the quality of refill dringking water treatment. This study uses a descriptive method with an observational design. The research variables were physical and bacteriological parameters. Samples were taken at three depots by direct observation, measuring physical conditions and taking water samples. The data were obtained at the depot and then analyzed in the laboratory. From the results of the test the turbidity level of the sample differs in the sample of 0,24, sample two with a turbidity level of 0,06 sample true with a turbidity level of the sample is different in sample on with a temperature level of 0,26 degrees celcius, while in samples two and three have the same temperature level of 0,27 degrees Celcius. Measurement on the physical quality of the smell and taste of refilled drinking water on samples one to three samples has met the requirements because it does not smell and taste. While the color test showed that thre was no difference in the color of the refilled drinking water from the drinking water depots. All samples met the reuirements as a source of drinking water based on the Minister of Health Regulation 494/Menkes/Per/IV/2010 concerning of refill drinkingwater in the city of Parepare.